Borrelia miyamotoi infection leads to cross-reactive antibodies to the C6 peptide in mice and men. (April 2020) - Koetsveld, J.; Platonov, A.E.; Kuleshov, K.; Wagemakers, A.; Hoornstra, D.; Ang, W.; Szekeres, S.; van Duijvendijk, G.L.A.; Fikrig, E.; Embers, M.E.; Sprong, H.; Hovius, J.W.
Abstract: Objectives: Borrelia miyamotoi is a relapsing fever Borrelia, transmitted by hard ( Ixodes ) ticks, which are also the main vector for Borrelia burgdorferi. A widely used test for serodiagnosis of Lyme borreliosis is an enzyme immunoassay (EIA) based on the C6 peptide of the B. burgdorferi sl VlsE protein. We set out to study C6 reactivity upon infection with B. miyamotoi in a large well-characterized set of B. miyamotoi disease (BMD) patient sera and in experimental murine infection. Methods: We performed in silico analyses, comparing the C6-peptide to immunodominant B. miyamotoi variable large proteins (Vlps). Next, we determined C6 reactivity in sera from mice infected with B. miyamotoi and in a unique longitudinal set of 191 sera from 46 BMD patients. Results: In silico analyses revealed similarity of the C6 peptide to domains within B. miyamotoi Vlps . Cross-reactivity against the C6 peptide was confirmed in 21 out of 24 mice experimentally infected with B. miyamotoi. Moreover, 35 out of 46 BMD patients had a C6 EIA Lyme index higher than 1.1 (positive). Interestingly, 27 out of 37 patients with a C6 EIA Lyme index higher than 0.9 (equivocal) were negative when tested for specific B. burgdorferi sl antibodies using a commercially available immunoblot. Conclusions: We show that infection with B. miyamotoi leads to cross-reactive antibodies to the C6 peptide. Since BMD and Lyme borreliosis are found in the same geographical locations, caution should be used when relying solely on C6 reactivity testing. We propose that a positive C6 EIA with negative immunoblot, especially in patients with fever several weeks after a tick bite, warrants further testing for B. miyamotoi .